The path as profane illumination. Walter Benjamin and Louis Aragon listening to the Surreal language of the street - Nicoletti, Olmo (Scenari, 2022)
The aim of this paper is to engage the Benjamin’s concept of “profane illumination”, starting from the experience of the walk in everyday life. In order to make this, the paper analyzes the relationship between Benjamin and the Surrealism, focusing on the concept of experience. In particular, we analyzed the influence of the déambulation surréaliste and of the walking experience in Louis Aragon’s Le paysan de Paris on the work of Benjamin. Despite the differences, summarized by the concept of awakening, it appears that for both of them the concept of the potential in everyday life can be found in a particular aesthetic experience of the streets and the landscapes.